Power division analysis of optical single mode branching waveguides - Mohamad Khazani Abdullah, (1995)
The power division behavior of single mode branching waveguides is studied theoretically. The dependence of the power division on the branching angle and on the coupling length is shown. A new qualitative formula relating these important parameters is presented. The calculated results for various power divisions are plotted. Certain power divisions are found to have certain respective limiting branching angles above which the desired power divisions can no longer be obtained